Organizational Justice: The Way it Works - JUNAID ATHAR KHAN; DR. SHAHID JAN (Journal of Business & Tourism, 2021)
Organizational justice has the potential to work in order to extract benefits for organizations and employees alike. If it implemented in full spirit will eventually improve commitment level improved job performance, more helpful citizenship behaviors, improved customer satisfaction, and diminished conflict. We demonstrate the management of organizational justice with some suggestions for building fairness into widely used managerial activities. These include hiring, performance appraisal, reward systems, conflict management, and downsizing.